Exploring the Nutritional Potential, Adaptive Traits, and Resilience of Four Mucuna Pruriens Varieties against Malnutrition in Southern Madagascar amidst the Challenges of Global Climate Change - Pierre, Rakotomamonjy; Erménégilde, Ralaibia Boniface; Rokiman, Letsara; Daniel, Razafindrazanakolona; Samuël, Randrianasolo Fenosoa; Riana, Razafindrakoto Fanoina Ny; Ngbolua, Koto-te-Nyiwa; Baholy, Robijaona Rahelivololoniaina (Budapest International Research in Exact Sciences (BirEx) Journal, 2025)
In the persistent pursuit of alleviating the deleterious effects of malnutrition, particularly accentuated in vulnerable regions such as southern Madagascar, a comprehensive examination of the inherent capacities of botanical resources emerges as imperative. The current investigation thus endeavors to delve into the nutritional intricacies and underlying adaptations of four distinct cultivars of Mucuna pruriens, with the overarching objective of elucidating potential avenues for addressing the enduring predicaments of malnutrition, which corrodes the socio-economic fabric of indigenous communities while being exacerbated by the adverse ramifications of global climatic shifts. This rigorous inquiry is poised to scrutinize the diverse cultivars of Mucuna pruriens extensively, meticulously analyzing their nutritional profile encompassing both micronutrient and macronutrient constituents. The fundamental aspiration of this scholarly endeavor is to elucidate the underexplored nutritional reservoirs harbored within these Mucuna pruriens varieties, presenting auspicious prospects for fostering a more equitable and sustainable dietary paradigm. This entails employing a series of preparatory measures including soaking, dehulling, germination, cooking, and drainage, aimed at mitigating the presence of anti-nutritional elements, thereby optimizing the nutritional utility of the seeds.